Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.51585/gjvr.2022.3.0047
|View full text |Cite
|
Sign up to set email alerts
|

Restoring healthy gut microbiome in poultry using alternative feed additives with particular attention to phytogenic substances: Challenges and prospects

Abstract: The majority of pathologies in poultry are linked to intestinal chronic inflammation due to a disbalance of the gut microbiota. Thus, a healthy microbiota drives the gut integrity, and the gut’s biological and metabolic functionalities, including efficacious use of nutrition, but also immunity, and neuroendocrine systems. However, many external factors are disturbing a stable, healthy gut microbiota. Heat stress, dysbiosis, leaky gut syndrome, and mycotoxins are the main “secret killers” in poultry that lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 94 publications
0
16
0
Order By: Relevance
“…Free radicals destroy cells and tissues, causing inflammation and disease. Antioxidants help to neutralize free radicals and protect cells from damage ( Shehata et al, 2022b ). Similarly, betaine supplementation has been shown to increase villi height in the duodenum of chickens by increasing the secretion of mucus and improving the integrity of the intestinal mucosal barrier in chickens under long-term heat stress ( Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free radicals destroy cells and tissues, causing inflammation and disease. Antioxidants help to neutralize free radicals and protect cells from damage ( Shehata et al, 2022b ). Similarly, betaine supplementation has been shown to increase villi height in the duodenum of chickens by increasing the secretion of mucus and improving the integrity of the intestinal mucosal barrier in chickens under long-term heat stress ( Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have studied the effects of EO on chickens under heat stress conditions ( Shehata et al, 2022b ; Yilmaz and Gul, 2023a ; Mangan and Siwek, 2023 ). These studies have shown that EO can improve performance, while reducing the negative outcomes of heat stress, such as reduced water intake, oxidative stress, and inflammation ( Chowdhury et al, 2023 ; Das et al, 2023 ; Rafeeq et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Phytogenic compounds have been evaluated as potential alternatives to antimicrobials in poultry [ 88 ]. However, the bioavailability, rate of absorption, and cost-effective delivery methods for phytogenic compounds make their feasibility and application on a commercial scale complicated [ 236 ]. The efficacy of phytogenic compounds has not been regulated since most of these compounds are generally accepted as safe by the US Food and Drug Administration.…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%
“…Although the biochemical structure of polyphenols results in their high biological activity as antioxidants in vitro, their biological efficiency in animals is hindered, due to the poor oral bioavailability of the polyphenols, which is explained by the contradictory findings from both in vivo and in vitro experiments [ 239 , 240 ]. The lower efficiency of polyphenols in vivo could be attributed to the following several factors [ 236 ]: (i) the low uptake and assimilation of polyphenolic substances may lead to insufficient minimal concentrations in target tissues, meaning they are not effective as scavengers of free radicals; (ii) the extensive biotransformation that occurs in the liver and intestinal tract may influence the functional forms of these substances, which in turn adversely impacts biological activities, including the antioxidant properties [ 142 ], and/or (iii) they may be metabolized and quickly eliminated from the bloodstream [ 241 ]. For these reasons, the observed in vivo antioxidant effects could be indirect effects that occur through the upregulation of antioxidant defenses by the substantial protective effect in the gastrointestinal tract and their effects on Nrf2 and NF-κB [ 140 ].…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation